PENGEMBANGAN LIFT THE FLAP SEBAGAI LEMBAR KERJA PESERTA DIDIK MENGGUNAKAN MICROSOFT EXCEL PADA PEMBELAJARAN METODE PERSEDIAAN FIFO, LIFO, AVERAGE KELAS XI AKL SMKL IPIEMS SURABAYA - Luluk Eka Novitasari,; Agung Listiadi, (Inspiratif Pendidikan, 2022)
The role of the Pessrta Didik Worksheet has an important influence to encourage enthusiasm and help students to increase broad material insights. the progress of times that are increasingly advanced by using sophisticated technology, student worksheets have experienced rapid development. The use of conventional Student Worksheets has begun to be shifted by modern Student Worksheets which are more effective, efficient, creative, and innovative.The research that is being developed uses the 4D model from Thiagarajan, namely the R&D research method which includes four stages, namely the definition stage, the planning stage, the development stage, and the dissemination stage. Research that is being developed uses two types of data, namely using verbal or qualitative data and using numerical data or quantitative data using open questionnaires and closed questionnaires, then the data will be interpreted based on the score table by Likert and Guttman scales. Research that is being developed is used to interpret its feasibility, to observe the development carried out by researchers and student assessments of Lift the Flap Student Worksheets using Microsoft Excel in learning the Fifo, Lifo, Average inventory method in class XI Accounting and Finance at Vocational High School Institutions.